Double the energy storage of hard carbon anode for Li-ion batteries via a simple blending strategy. (10th March 2020) - Zhong, Xingguo; Wei, Yaqing; Guo, Yanpeng; Cui, Can; Zhai, Tianyou; Li, Huiqiao
Abstract: Blending two materials together to improve electrode performance has been proven an effective and practical strategy in the battery industry. Herein, we fabricate a novel n-HC/GeP5 composite that doubles the energy density over hard carbon (HC) without sacrificing cycle stability and rate performance. The GeP5, with high capacity (2289 mAh g −1 ), ultra-high conductivity (2.4*10 6  S m −1 ) and high initial coulombic efficiency (ICE > 90%), enables it serve as an effective additive to HC at a low weight percent. By introducing 20% wt GeP5 by mass ratio into HC, the obtained n-HC/GeP5 -20%wt composite improves the reversible capacity from 400 mAh g −1 to 898 mAh g −1, and improves ICE from 74% to 85%. In addition, the rate capability of n-HC/GeP5, with 516 mAh g −1 and 64% retention comparing 1C–8C, is much better than that of pure HC (273 mAh g −1, 54% retention). Consequently, when tested at 1C and 8C for 550 cycles, large reversible capacity of 575 mAh g −1 and 400 mAh g −1 respectively can still be obtained for this n-HC/GeP5 -20% hybrid, revealing its great potential to be used in commercial battery products. Highlights: A unique blending strategy was proposed by integrating GeP5 into HC. The HC/GeP5 doubles the capacity from 400 mAh g −1 to 898 mAh g −1 over commen HC. The ICE can be improved from 74% (HC) to 85% (HC/GeP5 ). The GeP5 additive doesn't sacrifice HC's cyclability and rate performances. The large capacity and high conductivity of GeP5 play important role in HC/GeP5 .